Assessing Toxicological Safety of EverX Posterior and Filtek Ultimate: An In-Depth Extractable and Leachable Study Under ISO 10993-17 and 10993-18 Standards - Aydinoglu, Aysu; Hepsenoglu, Yelda Erdem; Yalcin, Can Ozgur; Sagir, Kadir; Us, Yesim Olcer; Eroglu, Seyda Ersahan; Yoruc, Afife Binnaz Hazar (AMER CHEMICAL SOC, 2025)
This study critically evaluates the biocompatibility and toxicological safety of EverX Posterior (eXP) and Filtek Ultimate (FU) dental composites following the International Standardization Organization (ISO) 10993-17:2023 and 10993-18:2020 guidelines. Our research highlights important findings on the depth of cure, water absorption, solubility, and release profiles of organic compounds in these composites using advanced chromatographic techniques. The analysis revealed that both eXP and FU composites are safe for patients regarding extractable and leachable (E&L) compounds, indicating a low risk of adverse biological effects. It was found that eXP and FU had solubilities of 6.062 +/- 0.576 and 0.864 +/- 0.436 mu g/mm3, respectively, revealing their stability and reliability for clinical use. Our results suggest that there is no significant difference in the release profiles of the uncured (dough) and cured forms of these materials. Also, the likelihood of systemic toxicological effects caused by the identified E and L compounds is considered to be low. This research emphasizes the compliance of these materials with strict ISO standards and highlights the importance of conducting extraction studies on both dough and cured forms for comprehensive toxicological safety assessments in dental practice.
Keywords: DENTAL RESIN COMPOSITES; BISPHENOL-A; FATTY-ACIDS; MONOMERS; RELEASE; QUANTIFICATION; ELUTION; DIMETHACRYLATE; POLYMERIZATION; COMPONENTS; Chemistry